Shadow Owners and Personalistic Power: Challenges in Tracing Corrupt Assets in the 2026 KPK Sting Operation Involving the Regent of Pekalongan - Amalia Syauket (KRTHA BHAYANGKARA, 2026)
Political corruption at the regional level has evolved from conventional bribery schemes to complex manipulation of corporate structures. This study analyzes the phenomenon of the Pekalongan Regent's Catch-and-Arrest Operation (OTT) to reveal how personalistic power facilitates the creation of shadow owners in regional strategic projects. Using a juridical-normative method with a case study and conceptual approach, this study dissects the abuse of formal authority through the practice of trading in influence. The research findings show: (1) Personalistic Power enables control of the procurement ecosystem through informal instructions that are impermeable to administrative traces; (2) Trading in Influence becomes an instrument for entrepreneurs to access projects, where the flow of benefits is channeled through family or staff nominees to break the chain of proof to public officials; (3) Obstacles to asset tracking arise due to the failure of digital systems to detect unusual financial profiles at the nominee layer. This study concludes that current beneficial ownership regulations are still a formality without legal teeth. Therefore, it is recommended that legal reconstruction be carried out through the independent criminalization of influence peddling in accordance with Article 18 of the UNCAC and the acceleration of the ratification of the Non-Conviction Based Asset Forfeiture instrument to tear down the veil of corporate secrecy that conceals illegal wealth.